Comparative Proteomic Analysis of Plasma Membrane Proteins in Rice Leaves Reveals a Vesicle Trafficking Network in Plant Immunity That Is Provoked by Blast Fungi - Zhao, Zhi; Li, Meng; Zhang, He; Yu, Yao; Ma, Lu; Wang, Wei; Fan, Yunxin; Huang, Ning; Wang, Xinying; Liu, Kunquan; Dong, Shinan; Tang, Haijuan; et al. (Frontiers in Plant Science, 2022)
Rice blast, caused by Magnaporthe oryzae, is one of the most devastating diseases in rice and can affect rice production worldwide. Rice plasma membrane (PM) proteins are crucial for rapidly and precisely establishing a defense response in plant immunity when rice and blast fungi interact. However, the plant-immunity-associated vesicle trafficking network mediated by PM proteins is poorly understood. In this study, to explore changes in PM proteins during M. oryzae infection, the PM proteome was analyzed via iTRAQ in the resistant rice landrace Heikezijing. A total of 831 differentially expressed proteins (DEPs) were identified, including 434 upregulated and 397 downregulated DEPs. In functional analyses, DEPs associated with vesicle trafficking were significantly enriched, including the “transport” term in a GO enrichment analysis, the endocytosis and phagosome pathways in a KEGG analysis, and vesicle-associated proteins identified via a protein–protein interaction network analysis. OsNPSN13, a novel plant-specific soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) 13 protein, was identified as an upregulated DEP, and transgenic plants overexpressing this gene showed enhanced blast resistance, while transgenic knockdown plants were more susceptible than wild-type plants. The changes in abundance and putative functions of 20 DEPs revealed a possible vesicle trafficking network in the M. oryzae-rice interaction. A comparative proteomic analysis of plasma membrane proteins in rice leaves revealed a plant-immunity-associated vesicle trafficking network that is provoked by blast fungi; these results provide new insights into rice resistance responses against rice blast fungi.